Accuracy of SenseWear Pro2 Armband to Predict Resting Energy Expenditure in Childhood Obesity. (2nd July 2013) - Predieri, Barbara; Bruzzi, Patrizia; Lami, Francesca; Vellani, Giulia; Malavolti, Marcella; Battistini, Nino C; Iughetti, Lorenzo
<x xml:space="preserve">Abstract</x> Objective: The accuracy of the SenseWear Pro2 Armband (SWA) in estimating resting energy expenditure (REE) in children and adolescents with obesity, using indirect calorimetry (IC) as a reference was evaluated. Design and Methods: REE was assessed using both the SWA and IC in 40 obese subjects (26 M/14 F, age 11.5 ± 2.57 years, z‐score BMI 3.14 ± 0.53). The agreement between methods was assessed by the Bland‐Altman procedure. The relationship between REE assessments and patients' characteristics was also analyzed. Results: SWA‐ and IC‐derived estimates of REE showed a significant correlation (r = 0.614; P < 0.001), but the SWA overestimated mean REE by 13% (P < 0.001). Age and kilogram of fat‐free mass (kg‐FFM) were significantly correlated with both REE estimation by SWA (r = 0.434 and r = 0.564, respectively) and IC (r = 0.401 and r = 0.518, respectively). Only kg‐FFM was demonstrated to be the main predictor factor of REE variability (r2 79% SWA; 75% IC). Conclusions: The SWA overestimated mean REE in childhood obesity, suggesting that the SWA and IC are not yet interchangeable methods. This would require improving the SWA by developing better algorithms for predicting REE and, probably, bias in each individual REE could be reduced by an adjustment for subjects' kg‐FFM.